Reproductive cycle of the European clam Ruditapes decussatus from Óbidos Lagoon, Leiria, Portugal. Issue 4 (2nd October 2018) - Machado, Daniela; Baptista, Teresa; Joaquim, Sandra; Anjos, Catarina; Mendes, Susana; Matias, Ana Margarete; Matias, Domitília
ABSTRACT: In Portugal, the European clam ( Ruditapes decussatus ) is an important commercial resource. Óbidos Lagoon is a strong candidate as a cultivation area to increase European clam exploitation. However, the reproductive biology of this population has not been described. In this work, the reproductive cycle of R. decussatus was characterized by determining gonadal development stages, gonad index, condition index, and biochemical composition. The relationship between reproduction and environmental parameters (sea surface temperature, chlorophyll a, and particulate organic matter) was assessed. Ruditapes decussatus had an annual reproductive cycle. The gametogenic cycle started in late winter, and the ripe stage in spring was followed by spawning that began at the end of spring/early summer and extended until early autumn. The subsequent period of sexual rest occurred during the winter. Condition index showed seasonal variations related to food availability (chlorophyll a ). The European clams in Óbidos Lagoon recovered rapidly after their reproductive period, most likely owing to the availability of food. This study will help to improve sustainable management of this wild stock and is important for future aquaculture development of this species.